Financial Assistance to Local Authorities – Practice and Problems - Nenkova, Pressiana (Research Papers, 2005)
Financial assistance to local authorities in bad economic state and impossibility to manage their financial obligations put many problems to be dealt with. They concern availability of financial difficulties and necessity of central assistance, and also creating proper normative and economic conditions to overcome and avoid difficulties. The main purpose of this paper is to discuss central assistance to municipalities from the perspectives of central government, as well as local authorities. A special attention is paid to the possibilities of using objective criteria of distinguishing legitimate cases from illegitimate ones for central assistance and building an adequate system of local finance. Various practical decisions have been submitted to get over the information asymmetry by using effective methods of monitoring. The last part of the paper consist of recommendations for building a working system for assisting local authorities in financial difficulties. The analysis made comes from the need of keeping financial discipline at local level and preventing from wasting public resources.